A longitudinal study testing the role of psychache in the association between emotional abuse and suicidal ideation. Issue 12 (30th August 2019) - Li, Xiaoan; You, Jianing; Ren, Yaxuan; Zhou, Jiazhi; Sun, Ruohan; Liu, Xiaoliu; Leung, Freedom
Abstract: Objective: Research suggests that emotional abuse is associated with adolescent suicidal ideation. But how they are related is still unclear. The present study tested the temporal relationship between emotional abuse and suicidal ideation, with psychache as the potential mediator. We also examined the reciprocal relationship between psychache and suicidal ideation. Method: A number of 2, 259 Chinese high school students (53.8% females, mean age = 15.11, SD = 1.57) in Hong Kong completed questionnaires assessing emotional abuse, psychache, and suicidal ideation three times at 6‐month intervals. Results: The results supported the mediating effect of psychache in the path from emotional abuse to suicidal ideation. In addition, psychache and suicidal ideation were related reciprocally over time. Conclusion: The findings of this study may help researchers and practitioners understand the pathways by which emotional abuse impacts adolescent suicidal ideation. Implications for preventions and interventions of suicidal ideation were discussed.